Neuroprotection New Approaches and Prospects - Otero-Losada, Matilde; Capani, Francisco; Perez Lloret, Santiago (IntechOpen, 2020)
Neurological disease affects nearly 25%-30% of the world's population, exerting enormous financial strain on the healthcare system. Estimated current costs are around $800 annual billion, and this number is expected to increase exponentially as the global population ages. As such, new and alternative neuroprotective strategies are urgently needed. This book examines some of the most promising approaches in neuroprotection as well as discusses current goals and prospects. Organized into three sections, chapters cover such topics as the use of cannabinoids, medicinal plants, and essential oils in Alzheimer's and Parkinson's; protein misfolding and the neuroprotective potential of vitamin E in cerebral ischemia; and potential new neurological treatments and their mechanisms of action.